Implementation of E-procurement policy in Bandung District - Firmansyah, Andrian; Halimah, Mas; Meisa Dai, Ratna (Technium Social Sciences Journal, 2021)
Along with the advancement of Information and Communication Technology in government administration, ideas emerge or from the development of e-governance to improve the quality of services to the public in the field of goods and services procurement so that they can be implemented effectively, efficiently, transparently, and accountably. In the context of realizing good governance in the concept of advances in information and communication technology (e-governance) in general are the ideals and hopes of the Indonesian nation. E-procurement is considered to be able to give the public confidence in the transparency and accountability of the goods and service procurement process. This trust can be built because the procurement process follows the provisions regulated electronically by prioritizing transparency and accountability so that providers who are determined to be tender or selection winners are providers of goods and services who have passed administrative and technical evaluations by participating in open competitions. This study uses a qualitative method with a descriptive analysis study approach, the findings of the analysis of the Electronic Procurement Service, the implementation of e-procurement policies with the direct procurement method is not optimally implemented, in practice it has not been fully implemented by e-procurement. This can be seen by what is planned in the General Procurement Plan against which the implementation of e-procurement is not by the objectives of implementing the e-procurement policy.